2000
DOI: 10.1366/0003702001950166
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Plant Carbohydrates and Changes in Leaf Carbohydrate Chemistry Due to Chemical and Enzymatic Degradation Measured by Microscopic ATR FT-IR Spectroscopy

Abstract: Leaf litter decomposition is largely effected by the enzymatic action of fungal colonizers of leaf material. Microscopic attenuated total reflectance (ATR) infrared spectroscopy would be a useful tool to evaluate changes in leaf litter carbohydrate chemistry over time during the colonization process at the scale of resolution of the fungal hyphae. This paper reports the first studies to use microspectroscopy in the mid-infrared (IR) region to perform analyses within an area of 250 × 250 μm to gain spectra of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…The samples had most likely absorbed moisture during storage as they were not kept in a moisture-free environment. This band showed a decrease after pretreatment followed by an increase after enzymatic hydrolysis up to 144 h. The absorption band at approximately 1030 cm À1 is characteristic for C-O stretching of an alcohol both in cellulose (Mascarenhas et al, 2000) and hemicellulose (Sun et al, 2000); the spectra showed an unexpected small increase in absorption after pretreatment and ½ h of enzymatic hydrolysis followed by a decrease after 8-144 h of enzymatic hydrolysis as would be expected. The results presented here are in general agreement with the trends seen by Kristensen et al (2008) on hydrothermally pretreated wheat straw.…”
Section: Spectroscopic Analysis Of Straw Sectionssupporting
confidence: 60%
“…The samples had most likely absorbed moisture during storage as they were not kept in a moisture-free environment. This band showed a decrease after pretreatment followed by an increase after enzymatic hydrolysis up to 144 h. The absorption band at approximately 1030 cm À1 is characteristic for C-O stretching of an alcohol both in cellulose (Mascarenhas et al, 2000) and hemicellulose (Sun et al, 2000); the spectra showed an unexpected small increase in absorption after pretreatment and ½ h of enzymatic hydrolysis followed by a decrease after 8-144 h of enzymatic hydrolysis as would be expected. The results presented here are in general agreement with the trends seen by Kristensen et al (2008) on hydrothermally pretreated wheat straw.…”
Section: Spectroscopic Analysis Of Straw Sectionssupporting
confidence: 60%
“…Infrared spectroscopy and X-ray diffraction could be useful tools for rapidly obtaining information about the structure of forage sorghum constituents and chemical changes occurring in various treatments. Previously, these techniques have been used to study structure and morphology of plant carbohydrates and lignocellulose [22,[25][26][27][28][29]. In this work, Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) were used to study changes in chemical composition and chemical structures after pretreatment and enzymatic hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…In the latter case, the loss of identifiable chemical components and the accumulation of distinctive degradation products (such as carbonyl containing species produced by oxidative processes) have been followed, and changes in microstructure deduced from spectroscopically-derived crystallinity indices [14], [15], [16].…”
Section: Introductionmentioning
confidence: 99%